2018
DOI: 10.12659/msm.910665
|View full text |Cite
|
Sign up to set email alerts
|

Silence of α1-Antitrypsin Inhibits Migration and Proliferation of Triple Negative Breast Cancer Cells

Abstract: Backgroundα1-antitrypsin (α1-AT) is highly expressed in many tumors. However, to the best of our knowledge, its relationship to triple negative breast cancer (TNBC) has not yet been studied. Thus, in this research we first explored the influence of α1-AT silencing on the abilities of migration and invasion, and then further study its molecular mechanism in TNBC cells.Material/MethodsThe viability of MDA-MB-231 cells were detected using cell counting kit-8 (CCK-8). The abilities of migration and invasion were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The fact that they reduce the expression of MMPs while increasing that of TIMPs makes HIV-protease inhibitors similar to natural compounds that perform these actions thanks to the same ability to hamper the AKT and MAPK signaling pathways [ 202 , 203 ]. Also, synthetic antagonists of α1-antitrypsin, an endogenous protease inhibitor which is overexpressed in tumor tissues, downregulate MMPs and, at the same time, upregulate TIMPs via PI3K/AKT inhibition [ 204 ]. It is worthy of note that the HIV-protease inhibitor ritonavir reduces α1-antitrypsin protein levels in treated patients [ 205 ].…”
Section: Mmp-9 Inhibitorsmentioning
confidence: 99%
“…The fact that they reduce the expression of MMPs while increasing that of TIMPs makes HIV-protease inhibitors similar to natural compounds that perform these actions thanks to the same ability to hamper the AKT and MAPK signaling pathways [ 202 , 203 ]. Also, synthetic antagonists of α1-antitrypsin, an endogenous protease inhibitor which is overexpressed in tumor tissues, downregulate MMPs and, at the same time, upregulate TIMPs via PI3K/AKT inhibition [ 204 ]. It is worthy of note that the HIV-protease inhibitor ritonavir reduces α1-antitrypsin protein levels in treated patients [ 205 ].…”
Section: Mmp-9 Inhibitorsmentioning
confidence: 99%
“…In diabetic retinopathy there is a downregulation of Akt activity affecting a large number of pathways related to diverse cellular processes; ultimately, the resulting imbalance promotes RGC apoptosis. In the literature there are reports stating that A1AT can downregulate the PI3K/Akt/mTOR pathway in breast cancer cells, where this pathway is increased [163,164]. However, there are other reports remarking the role of A1AT as an up-regulator of the PI3K/Akt pathway, reducing neutrophil elastase-induced migration of lung cancer cells, tumor tissue proliferation and inflammatory microenvironment [161,162].…”
Section: Protein Kinase Bmentioning
confidence: 99%
“…An increase in AAT expression may also contribute to activation of signaling events that initiate the production and release of pro-inflammatory cytokines and adhesion molecules, such as lipopolysaccharides, TNF-α, IL-1 and IL-6, which are released by neutrophils, monocytes, macrophages and alveolar macrophages that may in turn activate innate immunity and inflammatory responses ( 13-15 ). A number of studies have suggested that AAT is associated with the development of chronic hepatitis, liver cirrhosis ( 16 ), chronic obstructive pulmonary disease ( 17 ), atherosclerotic diseases ( 18 ), tumors ( 19 ) and autoimmune diseases ( 20 ).…”
Section: Introductionmentioning
confidence: 99%